2017
DOI: 10.4067/s0717-95022017000300009
|View full text |Cite
|
Sign up to set email alerts
|

Upper and Lower Lip Soft Tissue Thicknesses Differ in Relation to Age and Sex

Abstract: SUMMARY:This study was performed to determine age-and sex-related differences in lip thickness. Lateral cephalometric images of 220 healthy individuals were taken and the thicknesses of the upper and lower lips were measured. The measurements were performed in three different age groups. Our results indicate that the lower lip thickness, as well as the distance between the most anterior point of contact between the upper and lower lips and the most protruding point of the upper incisor teeth, differed between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…In another study by Miron H et al 9 the maxillary lip at rest was found to be 3 mm shorter in females than the males and the authors attributed the differences to the simple biologic scaling clearly indicating sexual dimorphism. Furthermore, the maxillary lip thickness is reported to be more in males than the females after 20 years of age, 21 which would have its impact over the parameters of NLA and LL. So, we specifically chose to include patients between 20 to 40 years which would also mean that the growth of the hard and soft tissues is nearing completion.…”
Section: Discussionmentioning
confidence: 99%
“…In another study by Miron H et al 9 the maxillary lip at rest was found to be 3 mm shorter in females than the males and the authors attributed the differences to the simple biologic scaling clearly indicating sexual dimorphism. Furthermore, the maxillary lip thickness is reported to be more in males than the females after 20 years of age, 21 which would have its impact over the parameters of NLA and LL. So, we specifically chose to include patients between 20 to 40 years which would also mean that the growth of the hard and soft tissues is nearing completion.…”
Section: Discussionmentioning
confidence: 99%
“…On average, the smile line was found to be 1.5 mm higher in women than in men 17 ; similarly, in the current study, the ULH was greater in males than in women, indicating a shorter smile line in women (see Table 1g). Although the concept of beauty has changed throughout the centuries, the thickness of the upper lip has always been a subject of interest and has importance in every culture 18 . These results may be beneficial to forensic anthropologists, plastic and reconstructive surgeons, and orthodontists.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study that compared the soft tissue cephalometric measurements among Malaysian Malays and Chinese, used the Holdaway analysis instead that merely measured the thickness of the lips (Noor et al, 2020). Though lip thickness is one of the major elements of facial aesthetics, it fails to portray the protrusiveness of the face as opposed to comparing the position of the lips to the nose and chin using the E-line (Prabu et al, 2012;Bozdag et al, 2017).…”
Section: How To Cite This Articlementioning
confidence: 99%